(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Climate Change is an area of environmental science that has been studied for many years. The fossil record has taught humankind much about conditions on Earth long prior to our arrival. We now live in a unique time in that our scientific abilities have not only given us a precise age of the planet, but of the universe itself